Implementation of entrepreneurial skills among FPTV catering students - Harun, Hairuddin; Ismail, Lisa Mariam Syawal; Ismail, Nur Azrin (Penerbit UTHM, 2021)
The Ministry of Entrepreneur Development launches the National Entrepreneurship Policy in the middle of the second quarter of 2019. The policy is a government effort to accelerate the country's economic growth and focus on the growth of the national entrepreneurship sector by 2020. According to the Minister of Entrepreneur Development, this policy is not only a guide to the Ministry of Entrepreneur Development but it covering all other ministries involved in entrepreneurial activities which at the same time can create over a million jobs in the next five years (Basaruddin, 2019). This policy shows that the government is committed to empowering entrepreneurship especially involving youths.